2020
DOI: 10.3389/fmed.2020.00255
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Uric Acid Status With Bone Mineral Density in Adolescents Aged 12–19 Years

Abstract: Aims: Evidence linking serum uric acid (sUA) and bone mineral density (BMD) in adolescents is very limited. To the best of our knowledge, only one report has focused on the relationship between sUA and BMD in adolescents. Thus, this study aimed to determine the association between sUA and total BMD in adolescents aged 12-19 years.Methods: A cross-sectional study was conducted on a sample composed of non-institutionalized US population from the National Health and Nutrition Examination Survey. Weighted multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…The study also confirmed no significant association between SUA and total body BMD in young adults, women, non-obese, and smokers. This finding is supported by several epidemiological studies using different study designs and population samples (23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) as listed in Table 2. These epidemiological studies aimed to elucidate the relation between SUA and bone health.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The study also confirmed no significant association between SUA and total body BMD in young adults, women, non-obese, and smokers. This finding is supported by several epidemiological studies using different study designs and population samples (23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) as listed in Table 2. These epidemiological studies aimed to elucidate the relation between SUA and bone health.…”
Section: Discussionsupporting
confidence: 63%
“…Consistently two longitudinal studies had concluded the positive association between SUA and annual rates of change in BMD at different skeletal sites ( 31 ) and lower risk in developing osteoporotic fractures ( 29 ). Interestingly, other studies had additionally confirmed the lack of association between SUA and BMD in young females ( 35 ) and black Americans ( 34 ).…”
Section: Discussionmentioning
confidence: 89%
“…At the hydrophilic condition, it shows the protective effects of antioxidants [38]. Reducing SUA could decline its protective effect to radiation damage [39], and total bone mineral density [40,41] or a protective effect on bone loss in rheumatoid arthritis [42] ( Figure 1). Beyond its role in protection, over-saturated SUA together with sodium could deposit in joints, soft tissues, bones, skin, etc., as MSU crystals to form tophi and trigger gout flares with episodes of severe pain.…”
Section: Uric Acid and Goutmentioning
confidence: 99%
“…At the hydrophilic condition, it shows the protective effects of antioxidants [ 38 ]. Reducing SUA could decline its protective effect to radiation damage [ 39 ], and total bone mineral density [ 40 , 41 ] or a protective effect on bone loss in rheumatoid arthritis [ 42 ] ( Figure 1 ).…”
Section: Uric Acid and Goutmentioning
confidence: 99%
“…At the hydrophilic condition, it shows the protective effects of antioxidant [38]. Reducing SUA could decline the protecting effect to radiation damage [39], and total bone mineral density [40,41] or a protective effect on bone loss in rheumatoid arthritis [42].…”
Section: Uric Acid and Goutmentioning
confidence: 99%